Multimedia Development of Android-based Referee Signals Recognition Application in Basketball Game for Beginner Players (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Understanding given through verbal and demonstration will be clearer if it is strengthened with developed multimedia. The use of media as a learning resource in basketball is very important, which provides opportunities for trainees or basketball extracurricular beginners to be actively involved directly through the developed media. The product development procedure includes analysis of the product to be developed, developing initial product, expert validation and revision, small group trial and revision, large group trial and final product. Data collection is carried out using questionnaires obtained from expert evaluations, and using field observations obtained from basketball training participants. Data analysis technique uses descriptive statistical analysis. The results of small group trial research that has been carried out, the categories obtained are